Genetic characterization of locally isolated yeast strain through mutagenesis study - Tan, Li Lung (2003)
Yeast biodiversity is considered to be almost untapped from a biotechnological viewpoint. Although Saccharomyces cerevisiae has been the most widely studied and exploited yeast species, other yeasts are fast emerging as microorganisms of important scientific and commercial value. In this research, five different yeast strains (isolated from several aquatic and food sources) were identified using API 20C AUX kit as belonging to the genus of Rhodotorula, Pichia and Candida. The isolate designated as YL3, was identified with high degree of confidence as a putative haploid strain of Pichia ohmeri. It has a rapid growth rate and was able to tolerate growth temperature of up to 42°C and salt osmolarity of 2.5 M NaCl. Subsequently, YL3 was chosen as the candidate strain for the investigation of its physiological and molecular characteristics. Mutants of YL3 were generated using UV mutagenesis to establish suitable genetic markers. The UV dose of 115 J/m² (that yielded 10% cell survival) was used for the large-scale irradiation. The screening of 3x 10³ UV -irradiated random mutants yielded seven auxotrophic mutant with different amino acid biosynthesis defects; twenty temperature-sensitive (ts) mutants; and sixteen osmotic-sensitive (os) mutants. The stable auxotrophic mutants were two adenine-deficient (SAx and 22Ax), one methionine-deficient (2Ax) and one histidine-deficient (2SAx). Among the ts mutation observed, three were absolute ts mutant (7D, 9D and 11A) which showed tight growth arrest at 37°C and 40°C. The os mutants showed varying growth sensitivity to NaCI concentrations of 100 mM to 2 M. The majority of the ts and os mutants showed abnormal cell morphology compared to the YL3 wild-type under the stressful conditions. Temperature and osmotic shift experiments revealed that two mutants, 9D (a ts mutant) and 3B (an os mutant), have showed profound decrease in cell viability at increased temperature and osmotic stress, respectively. Interestingly, 75% of the os mutants simultaneously showed ts phenotype, indicating a close relation between the two sets of mutations. Further characterization of 9D using 4',6-diamidino-2- phenylindole (DAPI) staining revealed that these cells formed chain-like morphology with each cell compartment contained multiple nuclei under temperature stress. It is evident that the normal cell division of 9D was strongly impaired.